Design and Evaluation of an Individually Simulated Mobility Model in Wireless Ad Hoc Networks - Tan, Desney; Zhou, Shuheng; Ho, Jiann-min; Mehta, Janek; Tanabe, Hideaki ((2002) Communication Networks and Distributed Systems Modeling and Simulation Conference 2002, 2002)
Since there has been little focus on systematically creating user mobility and communication pattern traces, researchers in the mobile networking community often propose personal models with which to validate their routing algorithms. This approach has two problems: (1) invalid conclusions may be drawn from overly simplistic or unrealistic models, and (2) it is difficult to compare performance results of different algorithms due to the variety of models used. We describe a novel approach to generate user mobility patterns with an individually simulated behavioral model. In this model, the overall mobility pattern is the result of the interaction between the behaviors of individual nodes. We show that this general-purpose framework can reliably reproduce existing mobility patterns as well as create useful new ones. The model is validated with the statistical characteristics of representative scenarios and through the simulation with the Dynamic Source Routing (DSR) protocol.